Enhancing rooting tobacco (Nicotiana tabacum) plant by loaded indole-3-butyric acid in alginate/chitosan nanocapsule: Enhancing rooting tobacco - Ghorbani, Masoumeh; Kahrizi, Danial; Arkan, Elham; Aghaz, Farank; zebarjadi, Alireza (Cellular and Molecular Biology, 2024)
Recently, nanocarriers have been utilized for encapsulating and sustained release of agrochemicals specifically auxins. Due to their potential applications such as increased bioavailability and improved crop yield and nutritional quality. Herein, the efficacy of alginate/chitosan nanocapsules as a nanocarrier for the hormone indole-3-butyric acid (IBA) loading and its effect on rooting tobacco plants has been carried out in the present study. The average particle size of IBA-alginate/chitosan nanocapsules was measured by Dynamic light scattering analysis at 321 nm. Scanning electron microscope studies revealed the spherical shape of nanoparticles with an average size of 97 nm. The average particle size of IBA-alginate/chitosan nanocapsules was measured by Dynamic light scattering analysis at 321 nm. The characteristic peaks of IBA on alginate/chitosan nanocapsules were identified by Fourier transform infrared spectroscopic analysis. Also, high efficiency (35%) of IBA hormone loading was observed. The findings indicated that the concentration of 3 mgL-1 of IBA-alginate/chitosan nanocapsules has the highest efficiency in increasing the rooting in tobacco (Nicotiana tabacum) plants compared to other treatments. According to our results, we can introduce alginate/chitosan nanocapsules as an efficient nanocarrier in IBA hormone transfer applications and their use in agriculture.